MicroRNAs targeting EGFR signalling pathway in colorectal cancer - Mlčochová, Jitka; Vychytilová, Petra; Němeček, Radim; Svoboda, Marek; Slabý, Ondřej (Journal of cancer research and clinical oncology, 2013)
MicroRNAs (miRNAs) are short, 18-25-nucleotide long, non-coding single-stranded RNAs, which are capable to regulate gene expression on post-transcriptional level through binding to their target protein-encoding mRNAs. miRNAs regulate individual components of multiple oncogenic pathways. One of them is epidermal growth factor receptor (EGFR) signalling pathway that regulates cell proliferation, differentiation, migration, angiogenesis and apoptosis. All these processes are deregulated in colorectal cancer (CRC). Moreover, EGFR has been validated as the therapeutic target in CRC, and monoclonal antibodies cetuximab and panitumumab are used in the therapy of patients with metastatic CRC. Because of the extensive involvement of miRNAs in the regulation of EGFR signalling, it seems they could also serve as promising predictive biomarkers to anti-EGFR therapy. In this review, we summarize current knowledge about miRNAs targeting EGFR signalling pathway, their functioning in CRC pathogenesis and potential usage as biomarkers.
Keywords: regulace genové exprese u nádorů; Colorectal Neoplasms; Gene Expression Regulation, Neoplastic; RNA Interference; Signal Transduction; Protein Kinases; kolorektální nádory; MicroRNAs; Biomarkers, Tumor; lidé; ErbB Receptors; RNA interference; proteinkinasy; erbB receptory; nádorové biomarkery; signální transdukce; mikro RNA; Humans